The role of informal learning spaces in promoting social integration and wellbeing in higher education - Geister, Susanne; Keser Aschenberger, Filiz; Çetinkaya-Yıldız, Evrim; Apaydın, Seval (Frontiers in Education, 2025)
The global mental health crisis, intensified by the post-pandemic context, calls for holistic approaches to wellbeing in higher education. While prior research highlights the relevance of physical learning environments for health, limited attention has been paid to how these spaces foster social and psychological outcomes. This study examines how informal learning spaces (ILS) contribute to student wellbeing through the mediating role of social integration, with a focus on students facing personal challenges (FPC). Drawing on Tinto’s social integration model and the person–environment fit theory, this study explores two key questions: (1) Does social integration mediate the relationship between ILS availability/accessibility and student wellbeing? (2) Does FPC moderate the relationship between ILS and social integration? A cross-sectional survey was conducted with 932 university students from Austria, Germany, Italy, and Türkiye. Results showed that social integration mediates the relationship between ILS and wellbeing (β = 0.09). Moderation analysis indicated that the relationship between ILS and social integration was stronger for students FPC (β = 0.12), who reported significantly lower social integration when ILS were less accessible. Our findings present novel empirical evidence linking the physical learning environment to social integration and wellbeing, particularly for students facing personal challenges. These findings call for ILS to be intentionally designed as inclusive, welcoming, and supportive spaces that promote equity and wellbeing in higher education.